Policy Effects of Anti-Immigrant Party Representation on Aid to Vulnerable European Union/European Economic Area Citizens. (February 2018) - Tyrberg, Maria; Dahlström, Carl
While anti-immigrant parties have been electorally successful in European parliaments, it is still unclear whether they have influenced policies. This article contributes by investigating the anti-immigrant party policy impact on a previously unexplored welfare policy area, that concerning the mobility of vulnerable European Union/European Economic Area citizens. In Sweden, the aid offered to these citizens varies a great deal in different municipalities. Furthermore, the largest anti-immigrant party (Sweden Democrats) has, unlike the mainstream political parties, preferences for a strict policy in line with so-called welfare chauvinism. Taking advantage of this subnational variation, our data give us a unique opportunity to investigate whether anti-immigrant party representation impacts welfare policy outcomes. The empirical findings show a negative correlation between Sweden Democrats' representation and the aid offered and indicates that municipalities where Sweden Democrats holds a pivotal position offer less aid to vulnerable European Union/European Economic Area citizens. The hypothesis that these effects are conditional upon the ideology of the ruling coalition is, however, not supported.